Clean water supply and diarrhea incidence in Kupang - Hubi Maria Padji; Sudarmadji Sudarmadji (Berita Kedokteran Masyarakat (BKM), 2017)
Rainfall, humidity, wind speed, availability of clean water and diarrheal cases in dry area of Kupang, IndonesiaPurpose: This study aimed to determine the relation of climate factors and the availability of clean water with the diarrhea occurrence in Kupang City from the years of 2011-2015.Methods: This study used an ecological study design with Pearson correlation with Spearman correlation tests and used secondary data consisting of diarrhea cases, water discharge, and climate data of Kupang City from 2011-2015.Results: The results of statistical analysis showed that variables that correlate with diarrhea occurrence in Kupang City were rainfall (p = 0.0001; r = -0.48), humidity lag1-3 (p = 0.000; r = -0, 5), wind speed lag2-3 (p = 0.000; r = 0,5 and clean water supply (p = 0.0002; r = - 0.47) while the air temperature variable had no correlation with diarrhea occurrence in Kupang city in 2011 -2015 (p value > 0.05).Conclusion: Based on the research results, it was concluded that the variables of rainfall, humidity lag1-3, wind speed lag2-3 and availability of clean water were correlated with the incidence of diarrhea in Kupang City from the years of 2011-2015.